Evaluation of disparities in hospitalisation outcomes for deaf and hard of hearing patients with COVID-19: a multistate analysis of statewide inpatient databases from Florida, Maryland, New York and Washington - Hiraku Kumamaru; Loren G Miller; Rie Sakai-Bizmark; Dennys Estevez; Emily H Marr; Jong Hyon Lee; Frank Wu (BMJ Open)
Objective Investigate whether deaf or hard of hearing (D/HH) patients with COVID-19 exhibited different hospitalisation outcomes compared with hearing patients with COVID-19.Design Cohort studySetting Statewide Inpatient Databases for Florida, Maryland, New York and Washington, for the year 2020.Participants Records of patients aged 18–64 years with COVID-19Primary outcomes and measures Differences in in-hospital death, 90-day readmission, length of stay, hospitalisation cost, hospitalisation cost per day, intensive care unit (ICU) or coronary care unit (CCU) utilisation and ventilation use were evaluated. Adjustment variables included patient basic characteristics, socioeconomic factors, and clinical factors.Results The analyses included 347 D/HH patients and 72 882 non-D/HH patients. Multivariable log-transformed linear regression models found an association of patients’ hearing loss status with longer length of stay (adjusted mean ratio (aMR) 1.15, 95% CI 1.04 to 1.27, p<0.01), higher hospitalisation cost (aMR 0.96, 95% CI 1.00 to 1.22, p=0.049) and lower hospitalisation cost per day (aMR 0.96, 95% CI 0.92 to 1.00, p=0.04). We did not detect any significant relationships with other outcomes.Conclusions Our findings suggest that higher hospitalisation costs were attributed to prolonged stays rather than costly interventions, such as ICU care. Communication barriers between healthcare providers and D/HH patients, coupled with providers’ cautious approach to discharging D/HH patients, may explain our findings.